Microstructure and mechanical properties of stainless-steel fabricated via pellet extrusion printing - Lee, Yi Heng (Nanyang Technological University, 2024)
In this study, the effects of printing parameters on the microstructure and mechanical properties of pellet extrusion printed 316L stainless steel was investigated. The investigation covers several steps which are necessary to producing parts from feedstock containing binders, namely: printing; debinding and sintering. This is followed by microscopy analysis, hardness, and tensile testing to evaluate the properties of the parts and the optimal parameters were determined. The printing parameters selected include infill pattern and infill density. Each parameter was varied to assess their influence on the final properties. Additionally, the debinding and sintering processes were optimized to eliminate visual surface defects. The results of this study will provide an understanding on the relationship between infill printing parameters on the properties of 316L stainless steel. Furthermore, the results will serve as a solid foundation for future advancements specific to the pellet extrusion 3D printing process.